Interactive Media Edpuzzle and Its Implementation in Teaching Vocabulary in New Normal Era - Endang Mastuti Rahayu; Pradana Bhaskoro (Universitas Pendidikan Mandalika, 2022)
The aim of this study was to describe the use of interactive media EdPuzzle in teaching vocabulary. Many students had difficulties finding the right vocabulary in conveying ideas because the learning media used by the teacher was not varied. In new normal era, the teacher must be good at choosing interactive media for teaching vocabulary. One of interactive media was EdPuzzle, because it could make the learning process to become interesting. This study was quantitative descriptive. The research subject was the 8th-I grade of students at SMPN 2 Taman which consisted of 33 students. In this study, the researchers used an observation guide and questionnaire to collect the data which were then analyzed descriptive quantitatively and in percentage terms. The result of observational data analysis showed that the interactive media EdPuzzle used in teaching vocabulary made students more active and the class become fun. The results of the questionnaire analysis showed that 54% of students agreed that teaching vocabulary using interactive media Edpuzzle helped them understand the text. The conclusion was that interactive media EdPuzzle could be used in teaching vocabulary, because students felt more enjoyable, interested, and excited, also easier to memorize the English vocabulary during learning process.